1972
DOI: 10.1063/1.1660931
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of film-thickness determination by oscillating quartz resonators with large mass load

Abstract: A one-dimensional acoustical composite-resonator model is used to study the behavior of a quartz-crystal resonator with large mass load. On the basis of this model, it is found that the exact relationship between the frequency shift and the added mass depends on the acoustic impedance of the deposited material. The experimental data for three materials (silver, copper, and lead) with different acoustic impedances are shown to be in good agreement with the theoretical predictions. The validity and limitations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
166
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(175 citation statements)
references
References 6 publications
4
166
0
2
Order By: Relevance
“…In general, the substance under investigation should have good adhesion to the QCM surface, should be homogeneously spread, and should be sufficiently rigid. 12,13 QCM may lose its high sensitivity in the absence of good adhesion or undergo additional frequency shifts in the case of soft sample due to dissipation of oscillation energy. 14,15 Large errors in the measurement may occur in the case of thick nonrigid layers due to the acoustic wave absorption by the soft load.…”
mentioning
confidence: 99%
“…In general, the substance under investigation should have good adhesion to the QCM surface, should be homogeneously spread, and should be sufficiently rigid. 12,13 QCM may lose its high sensitivity in the absence of good adhesion or undergo additional frequency shifts in the case of soft sample due to dissipation of oscillation energy. 14,15 Large errors in the measurement may occur in the case of thick nonrigid layers due to the acoustic wave absorption by the soft load.…”
mentioning
confidence: 99%
“…For thick films such as those studied here, the effect of the coating elasticity on the system's acoustic impedance must be taken into account. Therefore, the mass change of the coated samples was calculated from the Z-Match method proposed by Lu and Lewis [183] which relates m L to the observed change in oscillation frequency through:…”
Section: In Situ Spe Evaluation Of Single and Multilayer Coatingsmentioning
confidence: 99%
“…Because the Sauerbrey equation does not take into account the change in elastic properties caused by the deposited film, the Z-Match method [183] is used for thick coatings where,…”
Section: In Situ Quartz-crystal Microbalance Spe Testingmentioning
confidence: 99%
“…The parameter ff is considered as the resonant frequency of the film if it were oscillating (Lu and Czandema, 1984). Lu and Lewis (1972) indicated that for precise mass determinations, the elastic properties of deposited material have to be taken into consideration. In the equation derived by Lu and Lewis, the resonant frequency of the composite system is determined by tIle acoustic properties of both the quartz crystal and the deposited film.…”
Section: Quartz Crystal Microbalancesmentioning
confidence: 99%
“…The Sauerbrey relation, Equation (28) was found to be valid up to a frequency change of about 2 % of the uncoated crystal frequency. Beyond that range the analytical expression developed by Lu and Lewis (1972) must be used.…”
Section: Viscoelastic Effects In Microbalance Applicationsmentioning
confidence: 99%